Circuit-analog radar absorbing structures using a periodic pattern etched on Ni-coated glass fabric. (1st February 2022) - Jang, Min-Su; Jang, Woo-Hyeok; Jin, Do-Hyeon; Choi, Won-Ho; Kim, Chun-Gon
Abstract: A circuit-analog broadband radar-absorbing structure with improved mechanical properties was proposed based on a periodic pattern etched on the Ni-coated fabric. Using the conventional polymer-based substrate as the resistive sheet of a conventional circuit-analog absorber, a decrease in the mechanical properties of the composite material was witnessed. Thus, we fabricated a periodic pattern fabric with a loop pattern using a nickel-coated glass fiber fabric and photolithography etching. Radar-absorbing structures exhibiting a >90% electromagnetic wave absorption performance in the broadband of the C- and X-bands (6–12.4 GHz) were designed using a genetic algorithm optimization. Three-point bending and tensile tests were then performed to evaluate their mechanical properties. Overall, the proposed radar-absorbing structures showed >90% absorption band of 6.7 GHz (6.3–13 GHz). In addition, these structures exhibited improved mechanical properties without deterioration in the interlaminar shear strength or tensile modulus compared to conventional circuit-analog radar-absorbing structures.